A study on factors that influence performance of contract employees in Majlis Perbandaran Port Dickson (MPPD) / Nur’ Afifah Kamaruzzaman and Nur Haryani Mohd Esa - Kamaruzzaman, Nur’ Afifah; Mohd Esa, Nur Haryani (Faculty of Business and Management, 2016)
This project paper focused on the research of "A study on factors that influence performance of contract employees in Majlis Perbandaran Port Dickson (MPPD)‟. The purpose of this research is to identify whether there is relationship between the dependent variable which are employee performance and independent variable which are organization culture, financial rewards and job content among contract employees in MPPD. Furthermore, the aim of this study is to identify the most important factor that influences employee performance. 118 sets of questionnaires have been distributed to the contract employees in order to fill out the entire questionnaire. This research paper is supported by secondary data which main gained from journals and articles. The researcher has used SPSS program to analyse data from the information gathered in order to get the result of this research. The findings show that organization culture is the most important factor that influence contract employees at the work place. Second followed by financial rewards and the least factor is job content that influence contract employees in MPPD.